Novel 2-mercapto imidazole and triazole derivatives as potent TGR5 receptor agonists - Sameer Agarwal; Santosh Sasane; Jeevan Kumar; Brijesh Darji; Hitesh Bhayani; Shubhangi Soman; Neelima Kulkarni; Mukul Jain (Elsevier, 2019)
TGR5 is a bile acid G protein-coupled receptor (GPCR), which is an attractive therapeutic target for the treatment of obesity, and its highly associated Type 2 diabetes. Activation of TGR5 promotes secretion of glucagon like peptide-1 (GLP-1) and activates insulin secretion. Series of novel 2-mercapto imidazole and triazole derivatives were designed, synthesized and evaluated for their activities as TGR5 agonists. Our medicinal chemistry efforts led to the identification of many potent compounds. In particular, triazole derivative 4m was able to stimulate hTGR5 receptors with an EC50 of 25 nM, and possess good physico-chemical profile. Keywords: TGR5, TGR5 agonist, Obesity, Type-2-diabetes, Imidazole derivatives, Triazole derivatives